KEPADATAN POPULASI KUTU DAUN (Myzus persicae) DAN PREDATORNYA (Monoshillus sexmaculata) PADA TANAMAN CABE (Capsicum annum) DI KECAMATAN KOTOPARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Dafrinal, Dafrinal; Widiana, Rina; Lusi, Armein (STKIP PGRI Sumbar, 2013)
Chili is a herbaceous plant of the family eggplant Solanaceae) which has the scientific name Capsicum annuum L. Chili has a lot of nutrients and vitamins, such as calories, protein, fat, carbohydrates, calcium, Vitamin A, Vitamin B1 and Vitamin C. Besides being used for domestic purposes, peppers can also be used for industrial purposes such as, industry-seasoning, food and medicine or herbal. Efforts to increase the production of chili still have problems due to pest aphids (Myzus persicae). Aphids reproduce in two ways: with and without marriage or their eggs can develop into young without fertilization (Partegonesis). This pests life cycle ranges from 7-10 days. These pests attack plants by sucking liquid chili leaves, shoots, flower stalks or other plant parts, so that the leaves become mottled yellow (chlorotic) and eventually fall so chili production declined. This insect will be clustered so as to cover part of the plant. Of control this pest than by using insecticides as well as biological control by predators. Predator beetles are found is the javelin (Menochillus sexmaculata). Has done research on leaf Mite Population Density (Myzus persicae) and the predatory beetle javelin (Menochillus sexmaculata) At Chilli plants. This study was conducted using a descriptive survey in April 2012, from the results, thepopulation density of aphids Myzus persicae with an average of 64.4 people per stick plant predatory beetles and javelin Menochillus sexmaculata with an average of 2.4 individuals per stick plant.